Effects of wild foods and food interventions in reducing the minimum cost of diet using linear programming modelling: a case study of Turkana in Kenya - Sarfo, J.; Termote, Céline; Keding, G.B.; Boedecker, J.; Pawelzik, E. (2017)
Poster presented at 3rd International Congress Hidden Hunger: Post-2015 Agenda and Sustainable Developmental Goals (SDG): Where are we now? Strategies to improve nutrition quality and combat hidden hunger, Stuttgart, Germany, March 20-22, 2017